Distant vision screening of schoolchildren as a practical method of applying telemedicine TO ophthalmology: results and prospects - V. V. Chernykh; I. L. Plisov; N. G. Antsiferova; V. B. Pushchina (Сибирский научный медицинский журнал, 2019)
Early detection of children sight disturbances allows ophthalmologists to prescribe in time preventive activities and treatment, to stop developing pathology, and to prevent complications initiation. The purpose of our study was to elaborate and introduce into practice a method of distant screening examinations of schoolchildren using telecommunication facilities. Material and methods. We developed an interactive computer program for distant examination of visual acuity, long or short sight shift in refraction , diagnostics of astigmatism and pathology of macular area. The results of the examination were automatically recorded in a computer database. The program was hosted on the clinic website. Examination was performed simultaneously for up to 5 schoolchildren sitting in a computer class of their schools. The examination lasted from 4 to 8 minutes for the group depending on the quantity of the invoked tests. Results and discussion. 28,983 schoolchildren underwent the distant screening of vision. Visual acuity of 1.0-0.9 was revealed in 14345 people (49.5 %), 0.8-0.2 - in 11187 people (38.6 %) and less than 0.1 - in 3451 people (11.9 %). The test is not specific in terms of the type of pathology, but it allows us to conclude that more than half of schoolchildren have a reduced vision. A method of distant screening vision examinations is reliable and high-performance. Database of the examination results is helpful to diagnose pathology at early stage, to track its dynamics and to inform parents in time on whether an expanded investigation and ophthalmological treatment of their children is necessary.